(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To assess efficacy of tadalafil or tamsulosin versus placebo for LUTS/BEP. Methods: This was a triple blind randomized control trial (RCT). This study was done on 150 cases of well controlled diabetic patients with LUTS/BEP after screening. The patients were >45 years of age, international prostate symptom score (IPSS) > 13, maximum urine flow rate (Qmax) 10-15 ml/sec. Selected patients were randomized in to 1:1:1 ratio to once-daily tadalafil 5 mg, tamsulosin 0.4 mg, or placebo for 12 weeks. Efficacy measures were assessed by IPSS, Qmax, post-voidal residue (PVR) in ultra-sonogram. Results: IPSS significantly improved versus placebo through 12 wk with tadalafil (-4.81; p<0.001) and tamsulosin (-4.03; p<0.001) and as early as 1 wk (tadalafil -2.04; p=0.001 and tamsulosin -2.14; p < 0.001). The IPSS Quality-of-Life Index improved significantly versus placebo with tadalafil (p<0.001) and with tamsulosin (p<0.001) but outcome was better with tadalafil. Qmax increased significantly versus placebo with both tadalafil (6.52 ml/s; p<0.001) and tamsulosin (6.64 ml/s; p<0.001). Adverse event profiles were consistent with previous reports. Conclusion: Monotherapy with 5 mg daily tadalafil or 0.4 mg daily tamsulosin resulted in significant and similar improvements versus placebo in IPSS+QOL in diabetic patients with LUTS/BEP staring from week one and maintained throughout the week 12. It However, Tadalafil also significantly improve Qmax. The adverse event profile was minimal and consistent with those previously reported with these drugs. Bangladesh Journal of Urology, Vol. 20, No. 1, January 2017 p.18-25